ADVENTURE ACTIVITIES IN NATURE AND DEVELOPMENT OF PRO-ENVIRONMENTAL BEHAVIOR: COMPARATIVE ANALYSIS BETWEEN ELDERLY PRACTITIONERS AND THEIR CONDUCTORS - Nery Chao, Cheng Hsin; Figueiredo, Juliana de Paula; Dias, Viviane Kawano [UNESP]; Fonseca, Cinthia Beatriz da; Oliveira Sobrinho, Ivan Igor de; Tavares, Giselle Helena; Schwartz, Gisele Maria [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2015)
This qualitative study aimed at comparing results regarding pro-environmental behavior of elderly practitioners and conductors of adventure activities. The Ecocentrism and Anthropocentrism Scale (THOMPSON; BARTON, 1994) was applied to intentional samples of elderly practitioners and young adult conductors of adventure activities in nature. Data were descriptively analyzed by content analysis and indicate that elderly and younger adults are included in the ecocentric dimension. However, the former are more anthropocentric and environmentally apathetic. New studies are suggested to subsidize new action strategies in the Human Motricity field, to stimulate the development of pro-environmental behavior.
Keywords: Nature; Elderly; Environmental Education